2012
DOI: 10.1029/2012wr012043
|View full text |Cite
|
Sign up to set email alerts
|

Analytical expressions for drainable and fillable porosity of phreatic aquifers under vertical fluxes from evapotranspiration and recharge

Abstract: [1] In shallow unconfined aquifers, the response of the water table (WT) to input and output water fluxes is controlled by two distinct storage parameters, drainable and fillable porosity, which are applicable for WT drawdown and rise, respectively. However, only the drainable porosity estimated from the hydrostatic soil moisture profile is in common use. In this study, we show that under conditions of evapotranspiration and/or recharge from or to a shallow water table, drainable and fillable porosity have dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(116 citation statements)
references
References 68 publications
3
112
0
1
Order By: Relevance
“…While S y,Soil varies with water table depth [Loheide et al, 2005;Acharya et al, 2012], we assumed that topographic variation at the landscape-scale limits this effect; that is, lower S y,Soil in areas of low elevation and higher water tables are modulated by higher S y,Soil in areas of higher elevations. We applied a constant S y,Soil for all water table depths following the equation in Laio et al [2009]:…”
Section: Climate Simulationmentioning
confidence: 99%
“…While S y,Soil varies with water table depth [Loheide et al, 2005;Acharya et al, 2012], we assumed that topographic variation at the landscape-scale limits this effect; that is, lower S y,Soil in areas of low elevation and higher water tables are modulated by higher S y,Soil in areas of higher elevations. We applied a constant S y,Soil for all water table depths following the equation in Laio et al [2009]:…”
Section: Climate Simulationmentioning
confidence: 99%
“…Due to the uneven distribution of percolation/applied irrigation, soil type and water table depth, there is an overlap in simulated groundwater recharge rates between loamy sand and loam: annual recharge for loamy sand averages $195 mm (standard deviation, SD of 55 mm); averages for loam of $108 mm (SD of 32 mm). The soil texture effects are analyzed assuming an exponential function modified from Acharya et al (2012):…”
Section: Impact Of Soil Texture On Rechargementioning
confidence: 99%
“…However, most previous studies equate drainage or percolation below the root zone and recharge at the water table and commonly ignore time lags between the two (e.g., Kendy et al, 2003;Lu et al, 2011). Although unsaturated storage change is generally affected by the root zone soil water content variations, a significant amount of stored water may change its status from saturated to unsaturated when the water table declines; and the deep unsaturated storage will play a more important role as the total storage capacity of the unsaturated zone increases (Bastiaanssen, 2003;Seibert et al, 2003;Acharya et al, 2012). Commonly used groundwater recharge estimation methods, such as soil water balance and unsaturated zone studies (e.g., natural and artificial applied tracer techniques) would overestimate recharge and underestimate the timing of recharge.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some cases of deviations between the groundwater level and soil water tension patterns showed that explicit inclusion of the unsaturated zone's storage is crucial for any investigation of shallow groundwater dynamics (cf. Acharya et al, 2012;Schwarzel et al, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…The groundwater level itself, being indicative of changes in the water storage and the sum of all water balance components, also shows typical diurnal fluctuations. Its amplitude is also influenced by the soil characteristics, especially the specific yield (Acharya et al, 2012;Loheide et al, 2005;Nachabe et al, 2004).…”
Section: Introductionmentioning
confidence: 99%